2006
DOI: 10.1002/kpm.265
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy and proposed codification of knowledge and knowledge systems in organizations

Abstract: This paper proposes a hierarchical taxonomy of knowledge and knowledge systems (KS) in organizations. The taxonomy is based on four criteria: structure (how knowledge is designed and what it contains); purpose (what is the knowledge for); function (what the knowledge does); and disciplinary content. Each criterion is further classified into distinct types of knowledge. The hierarchical taxonomy is then codified by means of a numerical system which serves to identity each type and unit of knowledge, down to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In the latter instance, web servers can combine content from various sources to create new content. Digital content is usually stored in repositories and knowledge bases, web, or file servers (Geisler, ) and needs to be stored and classified systematically to be of use to individuals and teams in the broader organizational context (Asprey & Middleton, ; Lynch, ; Selwyn, ). Research has shown that digital content creation is at the heart of knowledge management and that valuable content (a) facilitates learning and knowledge transfer, and (b) counteracts the loss of valuable organizational knowledge (Bosua & Venkitachalam, ).…”
Section: Background Of Content Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter instance, web servers can combine content from various sources to create new content. Digital content is usually stored in repositories and knowledge bases, web, or file servers (Geisler, ) and needs to be stored and classified systematically to be of use to individuals and teams in the broader organizational context (Asprey & Middleton, ; Lynch, ; Selwyn, ). Research has shown that digital content creation is at the heart of knowledge management and that valuable content (a) facilitates learning and knowledge transfer, and (b) counteracts the loss of valuable organizational knowledge (Bosua & Venkitachalam, ).…”
Section: Background Of Content Managementmentioning
confidence: 99%
“…From an infrastructure aspect, it is essential to consider the adoption and use of appropriate technologies/platforms for digital content classification. This calls first for proper content categorization of large amounts of digital organizational content or codified knowledge (i.e., Exhibit 2 highlights categorization) (Geisler, ). Secondly, robust integration of different content management technologies that are adopted and mechanisms that drive the development of training programs pertaining to the use of these new technologies in organizations.…”
Section: Final Conclusionmentioning
confidence: 99%
“…From its origins in the classification of living things, the idea of taxonomy now has universal applications in grouping knowledge so that it can be systematically developed, stored and re-used. In the information sciences, the study of corporate taxonomies has been a subject of considerable and longstanding interest among both researchers (Cheung et al 2005;Geisler 2006;Gruber 1993;Noy and McGuinness 2001;Saeeh and Chaudhry 2002) as well as practitioners (Conway and Sligar 2002;Delphi 2002;Ernst & Young;Gilchrist and Kibby, 2000;Gilchrist 2001;Greif 2001;Lehman 2003;Pepper 2000;Potter 2001;Woods 2004).…”
Section: Principles Of Corporate Taxonomiesmentioning
confidence: 99%
“…In the continuation of above bloom taxonomy, bloom's digital taxonomy was developed in which domain of learning are further elaborated as low order thinking skill and high order thinking skill (Churches 2012). Taxonomy was applied in knowledge and knowledge system in organization where taxonomy was based on four criteria namely structure (how knowledge is designed and what it contain), purpose (what is knowledge for), function (what the knowledge does) and disciplinary content (Geisler 2006). Taxonomy development for knowledge management was also described in seven steps which include define requirements, identify concepts, develop draft taxonomy, review with user and SMEs (Subject Matter Experts), refine taxonomy, apply taxonomy to content and finally manage and maintain taxonomy (Whittaker and Breininger 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As well as identifying similarities and differences among repair processes, helps in clear understanding of repair field to overcome confusion and difficulties in exploring (Bolden et al 1997). Repair processes coding as well as exploration of knowledge domains can be easily done (Geisler 2006). Taxonomies are very costly to maintain in contrary to value when it is detailed at large (Whittaker and Breininger 2008).…”
Section: Introductionmentioning
confidence: 99%